miR-EdiTar: a database of predicted A-to-I edited miRNA target sites. - Laganà, Alessandro; Paone, Alessio; Veneziano, Dario; Cascione, Luciano; Gasparini, Pierluigi; Carasi, Stefania; Russo, Francesco; Nigita, Giovanni; Macca, Valentina; Giugno, Rosalba; Pulvirenti, Alfredo; Shasha, Dennis; et al. (Bioinformatics, 2012)
MOTIVATION: A-to-I RNA editing is an important mechanism that consists of the conversion of specific adenosines into inosines in RNA molecules. Its dysregulation has been associated to several human diseases including cancer. Recent work has demonstrated a role for A-to-I editing in microRNA (miRNA)-mediated gene expression regulation. In fact, edited forms of mature miRNAs can target sets of genes that differ from the targets of their unedited forms. The specific deamination of mRNAs can generate novel binding sites in addition to potentially altering existing ones. RESULTS: This work presents miR-EdiTar, a database of predicted A-to-I edited miRNA binding sites. The database contains predicted miRNA binding sites that could be affected by A-to-I editing and sites that could become miRNA binding sites as a result of A-to-I editing. AVAILABILITY: miR-EdiTar is freely available online at http://microrna.osumc.edu/mireditar. CONTACT: alessandro.lagana@osumc.edu or carlo.croce@osumc.edu SUPPLEMENTARY INFORMATION: Supplementary data are available at Bioinformatics online.
Keywords: Adenosine; Binding Sites; Databases, Genetic; Gene Expression Regulation; Humans; Inosine; Internet; MicroRNAs; Nucleic Acid Conformation; RNA Editing